STUDI DESKRIPTIF IMPULSE BUYING PADA KOSMETIK DI KALANGAN MAHASISWI PSIKOLOGI - Kharisma Mawaddah Hakiki; Endang Supraptiningsih; Stephani Raihana Hamdan (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2018)
Cosmetics are identical with women, influences from fellow women could encourage someone to buy cosmetics. Faculty with the majority of female students is the Faculty of Psychology with ratio of women and men reached 4: 1, found complaints to female students associated with unplanned purchase of cosmetics which is an indication of impulse buying among female students. The purpose of this study is to obtain empirical data on how to desribe impulse buying on cosmetic products among female students Faculty of Psychology. The method used in this research is descriptive study. The samples in this study were 98 students of Faculty of Psychology through purposive sampling technique with student criterion of 2013-2017 class aged 18-25, who experience unplanned cosmetic purchases. Data collection techniques were carried out by distributing questionnaires derived based on the theory of impulse buying Verplanken & Herabadi (2001) and interviews as supporting data. Researcher found out of 98 female students, 69% (68 people) have high impulse buying behavior, which shows the behavior of irrational purchases by female students, which is associated with the unexpected and sudden purchase of cosmetic products, which is initiated on the spot when browsing cosmetic products so as to generate strong urge and feelings of enjoyment and the passion to buy cosmetics that are recognized through two aspects, namely cognition and affective. Researcher found factors that influence impulse buying are the marketing environment (discounts and attractive cosmetic stores), situational variables (availability of money), and personal variables (shopping with friends and in positive mood situation). It is concluded that both cognitive and affective aspects play a major role in impulse buying